Funding University Libraries: The Way Out - Antwi, I.K. (Ghana Library Journal, 1997)
Ghana has five functioning universities. These are the University of Ghana, Legon; Kwame Nkrumah University of Science and Technology, Kumasi (KNUST); University of Cape Coast (UCC); University for Development Studies, Tamale (UDS); and the University College of Education, Winneba (UCEW) respectively. The oldest and largest is the University of Ghana which was established in 1948 as the University of the Gold Coast and prepared students for the degrees of the University of London. The University of the Gold Coast became autonomous on October 1, 1961 and was renamed University of Ghana. Currently the University of Ghana has five faculties, four schools and eight institutes.